Hortos Florestais da Estrada de Ferro Sorocabana: subsídios para a gestão e conservação do Horto Florestal de Andrade e Silva (atual Estação Ecológica de Avaré) - Primos, Mariana Patty Guilger [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
O presente trabalho resgata a história da Ferrovia Sorocabana e mapeia alguns dos antigos hortos implantados pela companhia no Estado de São Paulo, visando aferir seus diferentes destinos. Metodologicamente, o trabalho se debruça em fontes documentais (Relatórios da Ferrovia, do Instituto Florestal, certidões de Cartórios e legislação), dissertações, teses e levantamentos in loco. Adota como estudo de caso o Horto de Andrade e Silva, atual Estação Ecológica de Avaré, analisando sua história, o Plano de Manejo, o bairro rural adjacente e, a partir de uma perspectiva comparativa com outros hortos estudado e o Plano Diretor do Município visa trazer subsídios para sua gestão e conservação, em uma visão integrada entre o estado e o município.

The present work recovers the history of Ferrovia Sorocabana and maps some of the old gardens implanted by the company in the State of São Paulo, aiming to assess their different destinations. Methodologically, the work focuses on documentary sources (Railway Reports, from the Forestry Institute, certificates from Notary Public Offices and legislation), dissertations, theses and on-site surveys. It adopts as a case study the Horto de Andrade e Silva, current Ecological Station of Avaré, analyzing its history, the Management Plan, the adjacent rural neighborhood and, from a comparative perspective with other studied gardens and the Master Plan of the Municipality aims to bring subsidies for its management and conservation, in an integrated vision between the state and the municipality.

The present work recovers the history of Ferrovia Sorocabana and maps some of the old gardens implanted by the company in the State of São Paulo, aiming to assess their different destinations. Methodologically, the work focuses on documentary sources (Railway Reports, from the Forestry Institute, certificates from Notary Public Offices and legislation), dissertations, theses and on-site surveys. It adopts as a case study the Horto de Andrade e Silva, current Ecological Station of Avaré, analyzing its history, the Management Plan, the adjacent rural neighborhood and, from a comparative perspective with other studied gardens and the Master Plan of the Municipality aims to bring subsidies for its management and conservation, in an integrated vision between the state and the municipality
Estrada de Ferro Sorocabana Forest Garden: subsidies for the management and conservation of the Andrade e Silva forest garden (current Avaré Ecological Station)
Keywords: Horto Florestal; Estrada de Ferro Sorocabana; Estação Ecológica; Forest Garden; Estrada de Ferro Sorocabana; Ecological Station